Highly permeable polyethersulfone hollow fiber gas separation membranes prepared using water as non-solvent additive - Wang, D.; Li, K.; Teo, W.K.
Polyethersulfone (PESf)asymmetric hollow fiber membranes with excellent gas separation properties were fabricated from spinning solutions containing PESf, N-methyl-2-pyrrolidone (NMP)and water. Water was also used as the external coagulant. The internal coagulants used include water, ethanol, 2-propanol, the mixtures of ethanol/water and 2-propanol/water. The spinning solutions were tailored to be close to the point of phase separation by the introduction of water. The influence of water as a non-solvent additive (NSA)on the properties of polymer solution, gas separation properties and membrane structures was examined. The hollow fiber membranes were characterized by gas permeation measurements and scanning electron microscopy. The effects of various spinning conditions including polymer concentration, length of air gap, non-solvent strength of the internal coagulant and post-treatment, on the permeation properties and structures of the resulting hollow fibers were investigated. The viscosity of the spinning solutions was dramatically increased with the presence of water as an NSA. Ultra-thin skinned PESf asymmetric hollow fibers with apparent skin layer thickness of around 420-600 Å as determined by gas permeation flux were prepared under suitable spinning conditions. After silicone coating to repair surface defects, these hollow fibers exhibited gas selectivity higher than that of the PESf dense film. The observed permeance and selectivity are higher than those of the PESf hollow fibers spun from NMP/alcohols and NMP/propionic acid solvent systems reported in the literature. The use of an internal coagulant with a moderate non-solvent strength has been shown to improve hollow fiber integrity and suppress macrovoid formation.
Keywords: POLYETHERSULFONE; HOLLOW FIBER MEMBRANE; GAS SEPARATION; N-METHYL-2-PYRROLIDONE; WATER AS AN ADDITIVE